Gate-controlled valley transport and Goos–Hänchen effect in monolayer WS2. (7th February 2017) - Ghadiri, Hassan; Saffarzadeh, Alireza
Abstract: Based on a Dirac-like Hamiltonian and coherent scattering formalism, we study the spin-valley transport and Goos–Hänchen-like (GHL) effect of transmitted and reflected electrons in a gated monolayer WS2 . Our results show that the lateral shift of spin-polarized electrons is strongly dependent on the width of the gated region and can be positive or negative in both Klein tunneling and classical motion regimes. The absolute values of the lateral displacements at resonance positions can be considerably enhanced when the incident angle of electrons is close to the critical angle. In contrast to the time reversal symmetry for the transmitted electrons, the GHL shift of the reflected beams is not invariant under simultaneous interchange of spins and valleys, indicating the lack of spin-valley symmetry induced by the tunable potential barrier on the WS2 monolayer. Our findings provide evidence for electrical control of valley filtering and valley beam splitting by tuning the incident angle of electrons in nanoelectronic devices based on monolayer transition metal dichalcogenides.